Development and validation of a novel prediction score for cardiac tamponade in emergency department patients with pericardial effusion. Issue 5 (7th November 2020) - Duanmu, Youyou; Choi, Daniel S; Tracy, Sam; Harris, Owen M; Schleifer, Jessica I; Dadabhoy, Farah Z; Wu, Justina C; Platz, Elke
Abstract: Aims: Determining which patients with pericardial effusion require urgent intervention can be challenging. We sought to develop a novel, simple risk prediction score for patients with pericardial effusion. Methods and results: Adult patients admitted through the emergency department (ED) with pericardial effusion were retrospectively evaluated. The overall cohort was divided into a derivation and validation cohort for the generation and validation of a novel risk score using logistic regression. The primary outcome was a pericardial drainage procedure or death attributed to cardiac tamponade within 24 h of ED arrival. Among 195 eligible patients, 102 (52%) experienced the primary outcome. Four variables were selected for the novel score: systolic blood pressure < 100 mmHg (1.5 points), effusion diameter [1–2 cm (0 points), 2–3 cm (1.5 points), >3 cm (2 points)], right ventricular diastolic collapse (2 points), and mitral inflow velocity variation > 25% (1 point). The need for pericardial drainage within 24 h was stratified as low (<2 points), intermediate (2–4 points), or high (≥4 points), which corresponded to risks of 8.1% [95% confidence interval (CI) 3.0–16.8%], 63.8% [95% CI 50.1–76.0%], and 93.7% [95% CI 84.5–98.2%]. The area under the curve of the simplified score was 0.94 for the derivation and 0.91 for the validation cohort. Conclusion: Among ED patients with pericardial effusion, a four-variable prediction score consisting of systolic blood pressure, effusion diameter, right ventricular collapse, and mitral inflow velocity variation can accurately predict the need for urgent pericardial drainage. Prospective validation of this novel score is warranted.